PENGARUH EFIKASI DIRI, KEPUASAN KERJA DAN MOTIVASI TERHADAP KINERJA GURU SDIT - T, Trisna Indayani; Yanti, Hera; Najmuddin, Najmuddin (Research and Development Journal of Education, 2024)
The aim of this research is to: 1) Analyze the direct influence of the variable between self-efficacy on Job Satisfaction, 2) Analyze the direct influence of the variable between Self-Efficacy on teacher work motivation, 3) Analyze the direct influence of the variable between Self-Efficacy on teacher performance through satisfaction work, 4) Analyzing the direct influence between variables between Self-Efficacy on teacher performance through work motivation, 5) Analyzing the direct influence between variables between self-efficacy, job satisfaction, and motivation simultaneous work on teacher performance. This research uses quantitative methods. Meanwhile, the population of this study was 180 and the sample for this study used the Slovin formula with a sample of 124 teachers. Data collection techniques using questionnaires and using the product moment formula. Meanwhile, the data analysis used is SPSS for Windows 24. The results of this research show that there is an associative causal relationship between exogenous variables and endogenous variables. This means that there is a positive direct influence between exogenous variables and endogenous variables. The direct influence between exogenous variables and endogenous variables can produce a model of SDIT Teacher Performance in Central Aceh Regency, Aceh Province which is influenced directly and indirectly.